THE INFLUENCE OF LEARNING MEDIA AND TEACHER'S PEDAGOGIC COMPETENCE ON LEARNING EFFECTIVENESS - Linda LESTARI (Journal of Education and Leadership in Education, 2022)
This research aims to determine, identify, and describe Learning Media (X1) and Teacher Pedagogical Competence (X2) on Learning Effectiveness (X3) at State Elementary Schools in Cengkareng Barat Village. The population in this study were teachers in 1 sub-district of Cengkareng Barat, with a random sampling technique and 15 schools and 188 teachers were selected. Then calculated using the slovin formula so that 128 teachers were obtained as research samples.. Data collection techniques using questionnaires, questionnaires and documentation instruments. The results of the study are (1) there is a direct positive effect of Learning Media (X1) on Learning Effectiveness (X3) by 72%. (2) there is a direct positive effect of Teacher Pedagogic Competence (X2) on Learning Effectiveness (X3) by 19,4%. (3) there is a direct effect of Learning Media (X1) on Teacher Pedagogic Competence (X2) by is 42%.